CHARACTERISATION OF INFLUENZA A (H1N1 AND H7N7) VARIANTS RESISTANT TO COMMERCIAL ANTIVIRAL DRUGS - Korotetskiy , I.S.; Zubenko , N.V.; Shilov , S.V.; Ivanova , L.N.; Shvidko , S.V.; Toxanbayev , R.D. (Eurasian Journal of Applied Biotechnology, 2015)
Here, we describe the adaptation of influenza strains A/FPV/Weybridge/78 (H7N7) and A/Swine/Iowa/30 (H1N1) to the derivatives of adamantane (Rimantadine) and the neuraminidase inhibitor (Tamiflu). To determine the stability of the resistance phenotype, mutant strains were <a href="http://lingvo-online.ru/ru/Search/Translate/GlossaryItemExtraInfo?text=%d0%bf%d0%be%d1%81%d0%bb%d0%b5%d0%b4%d0%be%d0%b2%d0%b0%d1%82%d0%b5%d0%bb%d1%8c%d0%bd%d0%be&translation=consecutively&srcLang=ru&destLang=en">consecutively passaged in the absence of antiviral drugs for 5 passages. The IC50 value for FPV_RTam and Sw_RTam was >0.3 mg/ml for Tamiflu and >0.1 mg/ml for Rimantadine, respectively. Furthermore, the thermal stability of haemagglutinin and neuraminidase activity was determined in the study. Analysis of the amino acid sequence revealed the presence of a S31N substitution in the M2 protein of the FPV_RRim mutant strain, and an A30T substitution in Sw_RRim, which is responsible for the development of Rimantadine resistance. A specific substitution in position N207S of the amino acid sequences of the M1 protein in FPV_RTam and Sw_RTam mutants was also observed. Taken together, the results suggest that the nature of drug resistance is a multigene character.